Inter-municipality translation scheme of best solid waste management practices for Dagupan City - Llamas, Rishi Arjun Nonnatus P. (2011)
This study aims to design an eclogical solid waste management (SWM) plan for the city of Dagupan, Pangasinan. The plan emphasizes on low cost source reduction strategies and non-conventional treatment and disposal alternatives that will suit the city's limited budget. The objectives were to gather baseline data on the city's solid waste, assess current SWM practices with emphasis on RA 9003 compliance and propose interventions for implementation.
Social surveys (formulation of questionnaires, household surveys, key informant interviews), waste analysis and characterization study (WACS), study area inspection, secondary data gathering, and assessment of existing facilities in other areas in Pangasinan were the methods used in this study.
The social survey showed that 97.3% of the respondents are aware of the ecological waste management program (EWAMP) of their city. 93.6% of the respondents segregate their waste and 73.5% are satisfied with the solid waste collection. 96.2% of the respondents pay for their waste collection.
Dagupan City, with an estimated population of 166,229 (2009), has 5 island barangays and 26 mainland barangays. The average household generation rate for the city is 0.28 kg/cap-day. The city has a total waste inflow of 50,299 kilograms per day. Only 30,727 kg end up in the dumpsite because the current waste flow diversion rate is 38.91%. WACS revealed that the municipal solid waste coming from the households were mostly plastics (23.6%), papers (22.8%), residuals (21.1%) and garden wastes(19.4%).
The city practices waste reduction at source by limiting the sale of plastics and styrofoam. They also practice recycling through their junk shops and materials recovery facilities (MRFs) but of the 31 barangays, only 10 barangays have their own individual MRFs. Composting is also practiced. The generated waste is transported to the open dumpsite situated near the Tondaligan neach front at Bonuan Boquig.
This study presents proven low cost and well documented SWM success stories from the neighboring town of Bolinao, Pangasinan. Dagupan City can learn from these examples and apply the technologies and practices that are appropriate for them. Dagupan City may try to adopt the SWM practices of Barangay Patar and Barangay Lucero for their mainland and island barangays, respectively. The city ,may also follow the way Bolinao built its sanitary landfill in Barangay Balingasay.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Refuse and refuse disposal -- Pangasinan -- Philippines